La maternidad y el desarrollo educativo de las adolescentes del colegio de bachillerato “Beatriz Cueva de Ayora” en el periodo actual - Burneo Rodríguez, Ana Gabriela (2025)
Adolescent pregnancy represents a public health problem worldwide, Latin America has the second highest pregnancy rate after Africa. This problem not only compromises the health of adolescents, but also their education, economy, emotional well-being and standard of living. The present project seeks to determine the influence of motherhood on the educational development of adolescents in the high school “Beatriz Cueva de Ayora” in the current period, through the theoretical and methodological foundation of the subject; investigation of causes and consequences of teenage motherhood and its influence on educational development; to finally design an intervention proposal for the prevention of teenage pregnancy. The methodology used was mixed, using survey and interview techniques; originally the population and sample was 21 people, 17 adolescent mothers and 4 analysts from the student counseling department (DECE); however, due to cases of academic desertion, the instruments were applied to a total of 16 people. The results indicate that the main cause of teenage pregnancy is the lack of emotional support and family supervision; The main consequence is the impact on the economy of the students, in addition to the emotional impact, and regarding the influence on educational development, there was a divided opinion, since although most of the respondents showed a drop in their performance and school participation, the percentage is slightly higher among those who say the opposite, it was also found that this situation not only affects the educational sphere, but also other key aspects of their lives, such as emotional well-being and the economy, which hinders their personal, academic and professional development